1991
DOI: 10.1111/j.1467-6486.1991.tb00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Divestiture as a Response to Competitive Position and Market Structure

Abstract: One theory of acquisition motivation holds that some acquisition activity is a defensive reaction to weak or deteriorating industry conditions and competitive position. Designated the 'defensive diversification hypothesis', this motive has not been tested directly by relating firms' competitive circumstances to their subsequent acquisitive behaviour. This study does so. Results show that a firm's prior circumstances are related to the intensity of both its acquisitions and divestitures, as well as the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Divestitures -which include the sale, spinoff or liquidation of resources by an ongoing corporation -are a critical mode of reconfiguration by which firms can modify their resource base. Much of the literature on divestitures has examined antecedents that drive firms' divestiture activity (Berry, 2010;Duhaime & Baird, 1987; e.g., Duhaime & Grant, 1984;Hopkins, 1991;R. O. Hoskisson & Johnson, 1992).…”
Section: Background: Rbv Divestitures and Performancementioning
confidence: 99%
“…Divestitures -which include the sale, spinoff or liquidation of resources by an ongoing corporation -are a critical mode of reconfiguration by which firms can modify their resource base. Much of the literature on divestitures has examined antecedents that drive firms' divestiture activity (Berry, 2010;Duhaime & Baird, 1987; e.g., Duhaime & Grant, 1984;Hopkins, 1991;R. O. Hoskisson & Johnson, 1992).…”
Section: Background: Rbv Divestitures and Performancementioning
confidence: 99%
“…Rather, it is likely to seek and exploit a profitable niche or sub-segment in the industry that it believes will secure returns, but will also check the escalation in rivalry. At the same time, incumbents can be expected to re-balance their product portfolio by engaging in long-term investments in promising new products that complement disputed product lines, effectively expanding product scope while lowering relatedness (Hopkins, 1991;Sirmon et al, 2007;Uhlenbruck et al, 2003). This allows incumbents to explore intertemporal economies of scope in order to maintain long-term competitive capabilities and rent-earning perspectives (Baden-Fuller & Volberda, 1997;Helfat & Eisenhardt, 2004;Ketchen, Snow, & Street, 2004b).…”
Section: Abroad-based Foreign Competition Attack and Incumbent Scope mentioning
confidence: 99%
“…Studies of business dynamics have demonstrated that reconfiguring resources via modes such as acquisitions, alliances, internal development, and divestiture influences firm performance (Capron, 1999; Mitchell, 2000, 2004;Moliterno and Wiersema, 2007). The studies show that the motivation to reconfigure a firm's resource base can come from two sources: financial distress, where struggling firms face pressure to reconfigure resources in attempts to increase their operating efficiency (Bibeault, 1982;Robbins and Pearce, 1992), and financial strength, where strong firms reconfigure resources to improve their competitive position (Hopkins, 1991;Montgomery and Thomas, 1988;Koza, Tallman, and Ataay, 2011). In addition to such firm-level sources, studies of international business and institutional environments have argued that the extent of market development strongly affects business strategy and performance (Nelson, 1995;Hoskisson et al, 2000;Cuervo-Cazurra and Dau, 2009).…”
mentioning
confidence: 94%